Discovery of pyrazinone based compounds that potently inhibit the drug-resistant enzyme variant R155K of the hepatitis C virus NS3 protease. Issue 12 (15th June 2016) - Belfrage, Anna Karin; Abdurakhmanov, Eldar; Åkerblom, Eva; Brandt, Peter; Oshalim, Anna; Gising, Johan; Skogh, Anna; Neyts, Johan; Danielson, U. Helena; Sandström, Anja
Graphical abstract: Abstract: Herein, we present the design and synthesis of 2(1 H )-pyrazinone based HCV NS3 protease inhibitors with variations in the C-terminus. Biochemical evaluation was performed using genotype 1a, both the wild-type and the drug resistant enzyme variant, R155K. Surprisingly, compounds without an acidic sulfonamide retained good inhibition, challenging our previous molecular docking model. Moreover, selected compounds in this series showed nanomolar potency against R155K NS3 protease; which generally confer resistance to all HCV NS3 protease inhibitors approved or in clinical trials. These results further strengthen the potential of this novel substance class, being very different to the approved drugs and clinical candidates, in the development of inhibitors less sensitive to drug resistance.